2013
DOI: 10.4028/www.scientific.net/msf.757.99
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Modified Nano Montmorillonite (MMT) in Polyurethane Coatings Based on Acrylic Copolymer and Trimer of Isophorone Diisocyanate

Abstract: This work presents the synthesis of acrylic copolymer and trimer of isophorone diisocyanate (IPDI) for preparation of polyurethane (PU) coatings. Further we have studied the effect of silane modified nano montmorillonite (MMT) on the properties of PU coatings. Nano MMT was modified by vinyltriethoxysilane (TEVS) coupling agent and incorporated in PU coatings made from acrylic copolymers and trimer of IPDI. Acrylic copolymer was synthesized in the laboratory using butyl acrylate (BA), methyl methacrylate (MMA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Among the layered silicates, montmorillonite (MMT) was one of the most widely utilized to fabricate clay-polymer nanocomposite, because of the high aspect ratio and high expansion capacity. [9][10][11] Previous studies showed that nanocomposites were improved on the crystallization, mechanical properties, and thermal stability by adding MMT. [12][13][14] Perrine et al [13] analyzed the structure and properties of PHB/MMT nanocomposites and found that an optimum MMT content of 1 wt% can improve elongation at break while maintaining a high stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Among the layered silicates, montmorillonite (MMT) was one of the most widely utilized to fabricate clay-polymer nanocomposite, because of the high aspect ratio and high expansion capacity. [9][10][11] Previous studies showed that nanocomposites were improved on the crystallization, mechanical properties, and thermal stability by adding MMT. [12][13][14] Perrine et al [13] analyzed the structure and properties of PHB/MMT nanocomposites and found that an optimum MMT content of 1 wt% can improve elongation at break while maintaining a high stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the nature of the ionization of hydrophilic groups in water, waterborne polyurethanes are classed as anionic, cationic, and nonionic. Ionic aqueous polyurethanes have been extensively investigated, and the anionic variety is now being produced commercially [ 12 , 13 , 14 , 15 , 16 , 17 ]. Cationic aqueous polyurethanes are typically synthesized by utilizing diols containing tertiary amine groups as chain extenders and quaternizing with alkylating agents or appropriate acids to produce water-soluble ionic groups.…”
Section: Introductionmentioning
confidence: 99%
“…In polymeric materials, polyurethane (PU) is a group of polymers with versatile and excellent physical, chemical, and mechanical properties, which increased their demand in the field of industrial coatings applications. The rapid research dealing with the development of renewable source based polymeric resins and performance enhancement for chemical resistance and anticorrosive nature in salt solution is in progress by adding metal nanoparticles like ZnO, TiO 2 , Al 2 O 3 , silica, and montmorillonite in PU coating formulations. Microencapsulation of a core has been utilized in various sectors, viz., self-healing coatings, , controlled release of pesticides, and drug delivery. , Presently, technologists have focused on development of a new shell material with better properties over conventional shells for microencapsulation of a self-healing agent.…”
Section: Introductionmentioning
confidence: 99%